Eastern Feminism and Resistance in World Literature: A Postcolonial Reading of Woman’s middle eastern writers - surtinawati, surtinawati; Kardiansyah, M. Yuseano Kardiansyah (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
This study examines Eastern feminism and resistance in Middle Eastern women's writings from a postcolonial framework. The purpose of this study explored how the women writers subverted the patriarchal concept and constructed their selves in literary narratives. This study adopted a Systematic Literature Review (SLR) technique to synthesis literature from academic databases, such as Google Scholar, JSTOR, and ProQuest based on several strict criteria for inclusion. The findings of the study demonstrate that writers, including Nawal El Saadawi, Hanan Al-Shaykh and Fatema Mernissi sketch powerful female figures who contest patriarchal standards and question the tension of tradition and modernity. Complex storytelling methods, including magical realism, metafiction and social symbolism, were employed to strengthen feminist arguments and social critique. They are also a platform for women’s collective consciousness in response to gender injustice. Yet obstacles remain, including those posed by the difficulty of publication and the hegemony of Western feminist discourse. This study's finish line reveals that Middle Eastern women's literature is not only a creative reflection of life but is also an agent of change which aims to reshape and recreate women's identity and struggle for gender equality on a universal scale.